Annotations and Historical Ethnography of Piura (1767), and the Yunga Peoples documented by a Spanish Jesuit, Mario Cicala, exiled by King Charles III - Espinoza Ortega, Pavel (2024)
This study provides a detailed perspective about northern Peru’s colonial history, highlighting local dynamics and the role of religious orders in documenting indigenous cultures. We focus on the work of Mario Cicala, a Jesuit who stayed in Piura in 1767 after being exiled by decree of King Charles III, and carefully documented the geography, social life, and customs of the Yunga people. His writings blend religious mission with ethnographic observation, offering unique insights into the interactions between social structures, religious practices, and eco nomic activities in the 18th century. This study facilitates a deeper understanding on the challenges faced by Piura society at that time, and how these local dynamics intertwined with a broader context of the Spanish colonial rule.